Nystagmus and abducens nerve palsy as an early presentation of non-alcoholic Wernicke encephalopathy - Darussalam, Siti Hajar; Mohd Isa, Muhammad; Md Saleh, Rafidah; Mohmood, Adzleen; Mohammad Razali, Amirah (Springer Science and Business Media, 2024)
Wernicke encephalopathy (WE) is a rare but life-threatening syndrome that is commonly associated with chronic alcoholism. It has also been found to be associated with malnutrition, prolonged parenteral nutrition, hemodialysis, hyperemesis gravidarum, gastroplasty, and AIDS. It usually presents as a clinical triad of confusion, ophthalmoplegia, and gait ataxia. Nystagmus is usually the most common and earliest ophthalmologic sign. We report a case of non-alcoholic WE in a patient who had prior bariatric surgery and was treated for malnutrition and sepsis, with nystagmus being the initial presentation. The MRI of the brain was normal. The diagnosis of WE was made clinically and was supported by the patient's symptomatic and clinical recovery following intravenous thiamine treatment. It is essential to highlight that a high level of suspicion is needed to diagnose non-alcoholic WE to allow the commencement of appropriate treatment and reduce morbidity and mortality rates related to this condition.